Sistem Kontrol Berbasis Pemrograman LabVIEW MyRIO untuk Monitoring Kualitas Udara Dalam Ruangan - Andrizal Andrizal; Lifwarda; Yul Antonisfia; Zulharbi; Yuhefizar (Ikatan Ahli Informatika Indonesia (IAII), 2020)
A multisensor control system based on the LabVIEW myRIO programming has been created for monitoring indoor air quality. The purpose of this research is to create a system to monitor and control the levels of CO and CO2 in the room so that it remains within the threshold of healthy air and does not endanger users. The research phase began with the manufacture of a multisensor circuit and a relay module for the air purifier system and connected to the input and output ports of the myRIO module as a processor programmed with LabVIEW. The process of testing the multisensor response and the activation response of the air purifier on-off is carried out in open areas and indoors by adding artificial air pollution. Besides, air quality control and monitor is also carried out when the level of CO or CO2 gas exceeds the threshold by increasing the number of users and set the air conditioner activation. From the results and data analysis, it was found that the system could be used as a monitor and control the indoor air quality as expected. The range of CO sensor readings is 7.46 ppm - 27.65 ppm and CO2 296.8 ppm - 1190.5 ppm. Air purifier on-off control response time to change of CO and CO2 are 7 and 6 seconds. The air purifier system is able to clean indoor air with a long activation time depending on the number users and the room air conditioner activation settings.